Classification of Nonallergic Rhinitis Syndromes With a Focus on Vasomotor Rhinitis, Proposed to be Known henceforth as Nonallergic Rhinopathy - Kaliner, Michael A (World Allergy Organization, 2009)
Many patients have nasal syndromes that are nonallergic and noninfectious and not caused by mechanical or anatomic abnormalities. There are at least 8 recognized nonallergic rhinitis syndromes: drug-induced rhinitis including rhinitis medicamentosa, gustatory rhinitis, hormonally induced rhinitis including the rhinitis of pregnancy, nonallergic rhinitis with eosinophilia syndrome, senile rhinitis, atrophic rhinitis, cerebral spinal fluid leak, and vasomotor rhinitis. Few studies have explored etiologic causes. These syndromes are distinguished by clinical characteristics, recognized triggering conditions, and concomitant observations such as nasal eosinophilia or cerebral spinal fluid leak. Until more specific subjective clinical characteristics and/or objective measures can better define and differentiate underlying causes for these disparate diseases, they will remain a murky group of overlapping syndromes.